An Example of a Country Assessment: Desertification Mapping in Italy - Riccardo G. Boschetto (Italian Journal of Agronomy, 2010)
Desertification is the result of human induced land degradation which can be accelerated under severe drought conditions, and can occur under very diverse climatic conditions. Actually, studies have been conducted on assessing the vulnerability to desertification in Italy at national and regional level and they are based on different methodologies to carry out maps. These methodologies are developed by combination of different climatic, soil, vegetation, and socio-economic attributes useful to estimate pressure on land and state of soil and vegetation. This study is aimed at sketching the methodologies used in the creation of the current available maps of the risk of desertification in Italy and the state of the art of the mapping tools as well as some limits of them: firstly, a complete absence of bias in each indices of the algorithm which gives vulnerability index, and secondly the extreme variability of indices in relation to the degree of precision from national to local scale.